Development of learning videos of atomic theory concepts of Tialo language - Filza Farhana; Sahrul Saehana; Lilia Halim (Momentum: Physics Education Journal, 2021)
The purpose of this research is to produce a video learning content on atomic theory. This research uses the design and development design that employs the ADDIE model. The research instrument used was a questionnaire with a four-likert scale admistered on content experts, linguists, media experts, teachers and 10 students of MA AL-KHAIRAAT Tomini. The validity of the content, language and media aspects was said to be good with scores of 3.25; 3.33 and 3.28 respectively. Meanwhile, the scores obtained from teachers and students of class XI IPA were 3.87 and 3.51, both of which were in the "Strongly Agree" category. The results showed that the atomic theory learning video in the Tialo language was suitable for use in learning activities and could increase the concentration level of students. The theoretical implications of this research, namely the instructional video can increase learning motivation in students and the practical implication is that the instructional video is used as resources for teachers and prospective teachers to be used in the learning process.